Gerenciamento de resíduos sólidos urbanos no Brasil : uma análise exploratória - Pasquali, Pâmela Bia (2020)
Solid waste management is one of the biggest environmental issues in Brazil, highly dependent on landfill as the main method of disposal. The objective of this work was to present an overview of the GRSU system in Brazil, proposing improvements to the process based on an exploratory analysis. Data collection was performed based on information provided by the ABRELPE and SNIS database. ABRELPE explored the Solid Waste Panoramas and SNIS the Diagnostics of Urban Solid Waste management, regarding the generation, collection and final disposal of urban solid waste in order to compare the current state of the Brazilian USWM with other countries. The influence of the Gross Domestic Product (GDP) on the Generation of Waste was analyzed, and it was observed that such indicators are directly proportional. Regarding the quantity generated compared to the quantity collected, it was observed that in 2018, Brazil still lives with the reality that 17,318 t / day of MSW generated are not even collected. The evolution of selective collection was analyzed based on the number of municipalities that have this type of service. As for the alternatives for the final disposal of Solid waste, these are divided in their entirety, practically, in three ways: dumps, controlled landfills and sanitary landfills. As improvements, it is suggested that the state regulates the system, the population, conscious and educated, is charged for the amount and types of solid waste generated and the system guarantees its economic-financial sustainability. As a result, selective collection and proper final disposal will be consequences of management.